Effects of large amounts of hydrogen on the fatigue crack growth behavior of torsional prestrained carbon steel (Fracture and Structural Integrity, 2015)
The effects of large amounts of hydrogen on the fatigue crack growth properties of torsional prestrained ferritic–pearlitic low-carbon steel were investigated. Hydrogen-precharged specimens were produced by conducting cathodic charge to the virgin material and to torsional prestrained JIS-S10C and JISS25C steels (hereafter S10C and S25C steels). Rotating bending fatigue tests were conducted in air at room temperature. Hydrogen content, CH, increased with torsional prestrain for both S10C and S25C steels; the CH of the torsional prestrained S25C steel precharged with hydrogen was lower than that of S10C at the same torsional prestrain. No clear difference between the maximum CH values of the torsional fractured S10C and S25C hydrogen-precharged steel specimens. With respect to crack initiation, there was no obvious difference between the uncharged and precharged specimens in spite of the large amount of CH induced by torsional prestrain. The acceleration of fatigue crack growth by hydrogen was the main cause of the decreased fatigue life. For the virgin material, hydrogen had no obvious effect on the fatigue crack growth rate. In contrast, for the torsional prestrained materials, the acceleration ratios, {(da/dN)H/(da/dN)U}, increased with the torsional prestrain and CH. However, {(da/dN)H/(da/dN)U} did not exceed the value of about 30, even when a large amount of hydrogen was charged (10.0 ? CH ? 30.3 mass ppm). A hydrogen content threshold was found; hydrogen content above this limit enhances the growth of the non-propagated crack, even for metals with lower hardness (HV < 200).
Keywords: Fatigue crack growth property; Non-propagating crack; Large amounts of hydrogen